Some Aspects of Nutrition and Moderate Body Weight Reduction in Lithuanian Olympic Sport Centre Female Basketball Players - Marius Baranauskas; Linas Tubelis; Rimantas Stukas; Edmundas Švedas; Laimutė Samsonienė; Diana Karanauskienė (Lithuanian Sports University, 2018)
Research background and hypothesis. Many athletes know the beneﬁ ts of low carbohydrate diets these days, but recently healthcare specialists have paid much attention to high carbohydrate diets and safer methods of losing weight. Research aim was to investigate Lithuanian Olympic Sport Centre female basketball players' (n = 10) actual and special nutrition and their physical condition. Research methods. Athletes' food records were analyzed and assessed. We determined plasma triacylglycerol, total cholesterol, LDL cholesterol, HDL cholesterol, glucose. Physical Working Capacity (PWC 170 ) test was conducted to determine aerobic ﬁ tness before and after moderate weight reduction. Research results showed that the basketball players received too little carbohydrates, linoleic acid, amino acid methionine and too much fat. Vitamins D, PP, B 1  and folic acid intakes were insufﬁ cient. During moderate bodyweight reduction basketball players signiﬁ cantly decreased in their BW (-2.2 ± 0.3 kg, p < 0.05), BF (-1.6 ± 0.3 kg, p < 0.05) and minerals (-0.1 ± 0.4 kg, p < 0.05), but they non-signiﬁ cantly decreased in BP (p > 0.05). Furthermore, lipid panels markers (triacylglycerol, total cholesterol, LDL cholesterol, HDL cholesterol) experienced non-signiﬁ cant improvements while glucose levels (p < 0.05) and PWC 170  (p < 0.05) resulted in signiﬁ cant decrease following a 12-day hipocaloric diet. Discussion and conclusions. The results indicate that hipoenergetic moderate weight loss at < 30 kcal· kg -1  · day -1 , < 5 g · kg -1  · day  -1  carbohydrate is not recommended for athletes as it can affect aerobic ﬁ tness. Keywords: nutrition, female basketball, bodyweight reduction.